The Digital Repositories and the Research in History of Education - Laís Paula de Medeiros Campos Azevedo; Ana Liziane Araújo da Paz; Maria Gabriella Guimarães da Silva; Olívia Morais de Medeiros Neta (Universidade Federal do Oeste da Bahia, 2020)
This article aims to present and discuss the use of Digital Repositories for research in the History of Education. We list six repositories for carrying out the study: the Brazilian Digital Hemeroteca, the Center for Research and Documentation of Contemporary History of Brazil (CPDOC), the History and Memory of Education Repository (RHISME), the Digital Repository TATU, the Institutional Repository of UFSC, and the Repository of the UFRN Image Laboratory (LABIM). We seek to understand and point out their functionalities, in addition to identifying the institutions to which they are linked and indicating possible lines of research involving the history of education from the documents made available. Access to files, libraries and other physical repositories is often difficult. The existence of digital repositories makes it possible to carry out research in different areas and, specifically, within the scope of the History of Education, contributing to the promotion and expansion of the field.